Medición del aporte de los inmigrantes al crecimiento económico: Algunos comentarios sobre la descomposición aditiva del producto interior bruto per cápita; Immigration economic growth contribution measurement to economic growth: Some comments on the additive decomposition of gross domestic product per capita - Rosa Maria Verdugo Matês; Xesús Pereira López; Manuel César Vila (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– This paper describes the impact caused by immigration on the estimated growth of gross domestic product per capita (GDPpc) in each of the countries of the 15 members of the European Union (EU-15) during the period 1995 to 2013. Specifically, GDPpc breaks down into three factors: labour productivity, employment rate and proportion of people of working age in the general population. To approximate the contribution of immigration to GDPpc growth, a disaggregated estimate for natives and foreigners is done. However, functions used in the relevant disaggregation can affect the findings regarding labour productivity, consequently care must be taken when measurement units of GDP are chosen.
Keywords: C00; E20; F22; O52; 330; international migration; GDPpc; productivity; employment rate; additive decomposition